Manners & mutiny - Carriger, Gail (Carriger, Gail. Finishing school, 2015)
In an alternate England of 1851, Sophronia Temminnick is the only hope for her friends, her school, and all of London when she must put her espionage training to the test to thwart an evil Picklemen plot.